Using restoration as an experimental framework to test provenancing strategies and climate adaptability. (15th September 2017) - Broadhurst, Linda; Prober, Suzanne; Dickson, Fiona; Bush, David
Summary: Restoring degraded Australian landscapes through revegetation is a key concern of land holders, NGOs and government agencies. With the advent of climate change, it is increasingly important that revegetation activities take into consideration the species and provenance of plant materials to ensure that environmental plantings will be resilient to future climate conditions. A major strength of the past 30 years restoration programmes is the development of a distributed network of educated and experienced practitioners. We have recently invited stakeholders from among this network to participate in a process to cost‐effectively build Environmental Research Infrastructure – a nationally distributed network of restoration plantings that explore a broad range of research activities including a better understanding of the adaptive responses of different species and provenances. This would also facilitate long‐term monitoring of change and adaptation across Australia, providing a wealth of information to inform future conservation and restoration programmes.